ANTI-INFLAMMATORY PROPERTIES OF METHANOLIC BARK EXTRACTS OF TERMINALIA BROWNII IN WISTAR ALBINO RATS - MBIRI, JANE W.; KASILI, SICHANGI; PATRICK, KISANGAU; MBINDA, WILTON; PIERO, NGUGI M. (International Journal of Current Pharmaceutical Research, 2016)
Objective: This study investigated the anti-inflammatory properties of methanolic bark extract of Terminalia brownii in Wistar albino rats (Rattus novegicus). Methods: The experimental animals were divided into six groups of five rats each; normal control, negative control, positive control and three experimental groups. Carrageenan was used to induce inflammation. Diclofenac was used as the reference drug, and the three experimental groups were treated with the extract at the dose levels of 50, 100 and 150 mg/kg bw. The extract was screened for the presence or absence of selected phytochemical secondary metabolites using standard procedures. Results: The methanolic bark extracts of T. brownii significantly [p Ë‚ 0.05] reduced the carrageenan-induced paw edema by between 1.57%-20.41% while diclofenac reduced it by between 11.12%-25.33%. Phytochemical screening of the extract indicated the presence of alkaloids, flavonoids, phenols, saponins, steroids and terpenoids. Conclusion: The present study revealed that T. brownii bark extract is a potential candidate for the development of a novel anti-inflammatory formulation.